Development of nutritious frozen dessert from fruit-fruit formulation: analysis of sensory and market survey/ Fatin Nadzirah Zakaria ... [et al.] - Zakaria, Fatin Nadzirah; Abdul Malik, Anis Sofea; Hashim, Nina Keterina; Dasiman, Razif (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Nowadays, demands for the nutritious food keep increasing. Consumers need products that can provide good nutrients, low calories, high fiber and giving satisfaction feeling and well-being. Frozen dessert products have been consumed a long time ago. However, it does not yet been considered as a nutritious product as it always known as a food that consist of high sugar and fat content. Thus, innovations have been done by developing nutritious frozen dessert snack from dates (Phoenix dactylifera) and combined with two combinations of fruits that potentially have high antioxidant properties and enhance flavors, 1) Mango (Mangiferaindica) and papaya (Carica papaya); 2) Mango and orange (Citrus sinensis); 3) Mango and dragon fruit (Hylocereuspolyrhizus) which can be act as nutrient dense snack with zero added sugar. The proximate study was conducted which includes determination of carbohydrates, protein, fat, crude fiber, moisture, ash and energy. Hedonic test of the sensory evaluation was performed to evaluate the sensory characteristics between three different flavors of frozen dessert which include color, texture, taste, sweetness and overall acceptance. Market survey of developed product also was determined to predict the acceptance and likelihood consumer. This experimental study was conducted at UiTM Puncak Alam. The overall nutrition composition of frozen dessert showing a good nutritional value for all three flavors. For sensory evaluation, there was a significant differences (p<0.05) on color between three flavors. However, there were no significant differences (p> 0.05) on texture, taste, sweetness and overall acceptance. From the market survey, the results showed that 89.2 % of consumer stated that this frozen dessert is marketable. The nutritious frozen dessert are not just a sugar free dessert, but also as antioxidant booster, lactose free products and contain high nutritional values for all consumers.